Self-reported specific learning disorders and risk factors among Hungarian adolescents with functional abdominal pain disorders: a cross sectional study - János Major; Szilvia Ádám (BMC, 2020)
Abstract Background Despite its increasing clinical significance and diagnostic challenges, little is known about functional abdominal pain disorders (FAPDs) in Central-Eastern Europe. In this paper, the prevalence and potential sociodemographic correlates of FAPDs among Hungarian adolescents are explored. Methods A cross-sectional, nationwide, questionnaire study in a representative sample of 657 adolescents has been conducted. With a response rate of 80.2%, 522/527 (99.1%) questionnaires were eligible for data analysis (N = 267, 51.1% girls, mean age 14.8, SD 2.4 years). The questionnaire included sociodemographic variables (age, sex, place of residence, marital status of the parents, family income, religion, educational level of parents), questions regarding self-reported specific learning disorders and the Questionnaire for Paediatric Gastrointestinal Symptoms Rome ΙΙΙ Edition. Results The prevalence of FAPDs was 11.9% (N = 62). FAPDs were significantly associated with female sex. Living in a county town showed a negative correlation with FAPD. Adolescents with self-reported arithmetic learning disorders had an 8.7-fold likelihood of FAPD (OR, 8.7; 95% CI (3.5-21.9). Adolescent girls reported pain in all subtypes of FAPDs more frequently than adolescent boys except functional abdominal pain syndrome. The most prevalent FAPD was abdominal migraine (N = 32, 6.1%), followed by irritable bowel syndrome (N = 24, 4.6%). Conclusions The prevalence of FAPDs in Hungary is similar to that reported worldwide, however, contrary to international data, abdominal migraine is the most frequently encountered FAPD in Hungary. In addition to well-known correlates of FAPDs, such as female sex and place of residence, arithmetic learning disorders have also been identified as correlating with the prevalence of FAPDs. Our results suggest culture-specific differences in the distribution of FAPDs, and confirm the significance of school performance indicators such as specific learning disorders as a correlate of FAPDs.